Analysis of discharge consistency and performance of a sugarcane billet planter with a side-conveyer - Thienyaem, Titinai; Saengprachatanarug, Khwantri; Ueno, Masami; Eizo, Taira (Engineering and Applied Science Research, 2016)
Sugarcane is an important economic crop in Okinawa Prefecture. Sugarcane billet planters have been widely used in Okinawa due to high labor costs and planting time limits. Most of them are powered by hydraulic systems to avoid ground wheel drive problems when working on high moisture heavy clay soils. This study aimed to evaluate the performance and discharge consistency of a sugarcane billet planter, YABIKU B600, operated in Minami Daito Island, Okinawa Prefecture. Ni28 cultivar seed cane was harvested and chopped to an average length of 21.8 cm using an Austoft TM2008 harvester. The field experiment was done with 3 replications. A video camera with a GPS logger was positioned over the hopper of the planter during the tests to examine the performance and planting consistency of the planter. The numbers of discharged billets in each frame were recorded to calculate the discharge index or planting rate. Moreover, the speed, GPS position and time of each activity were collected to obtain the field capacity and field efficiency of the planter. The results showed that the average ground speed of the planter was 0.97 m/s. The field capacity was 0.24 ha/hr with a field efficiency of 45.66%. The average discharge index was 7.2 billet/m. The precision index averaged 24.63% with a discharge index range of 8-10 billet/m.